2015
DOI: 10.1007/s11748-015-0579-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on outcome of resected lung adenocarcinoma

Abstract: The smoking was significantly predictive of an unfavorable prognosis after surgery for lung adenocarcinoma. It is suggested that smoking is associated with serum CEA level, histologic subtype and GGO, resulting in unfavorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Recent studies have showing that smoking was a significant predictive for unfavorable prognosis in lung adenocarcinoma (26). And it was robustly associated with GGO growth (27).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have showing that smoking was a significant predictive for unfavorable prognosis in lung adenocarcinoma (26). And it was robustly associated with GGO growth (27).…”
Section: Discussionmentioning
confidence: 97%
“…The cumulative amount of alcohol consumption (g) was calculated as a product of daily alcohol consumption (mL) × alcohol percentage × 0.8 (g/mL) × duration of use (days). BI is a product of the number of cigarettes per day × duration of use (days) [7, 8]; BI and cumulative alcohol consumption were calculated based on the data recorded during the patient interview.…”
Section: Methodsmentioning
confidence: 99%
“…Available bioinformatics analyses can be a powerful tool for identifying biomarkers and therapeutic targets related to tumour progression and treatment. Previous studies have shown that novel serum biomarkers, including serum exosomes ( 27 29 ) and serum CEA ( 30 33 ), are good predictors of prognosis in lung adenocarcinoma. In addition, serum biomarkers related to inflammatory response are also good predictors of lung adenocarcinoma prognosis ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%